Profil Pedagogical Content Knowledge (PCK) Mahasiswa Calon Guru Matematika Ditinjau dari Kemampuan Akademiknya - Maryono, Maryono (UIN Sunan Ampel Surabaya, 2016)
The research of Pedagogical Content Knowledge (PCK) uses a qualitative approach with case studies. The purpose of this research is to obtain the Pedagogical Content Knowledge (PCK) of prospective teachers of mathematics in terms of academic ability. Data were analyzed in the form of documents and interview with the subjects were prospective teachers of mathematics in IAIN Tulungagung and STKIP PGRI Tulungagung. The results showed that a group of students with excellent academic ability and a group of students with good academic ability, content knowledge, knowledge of teaching, and knowledge of students are relatively same. Most of the content knowledge at level 1, knowledge of teaching at level 2, and knowledge of students at level 1. While the group of students with academic ability can reasonably be concluded that content knowledge at level 0, knowledge of teaching at level 1, and knowledge of students at level 1.